Native bamboo Arundinaria gigantea restoration for climate smart land management: A review - Sanjeev Sharma; D Alexander Wait; Churamani Khanal; Puskar Khanal (Advances in Bamboo Science)
Bamboo, a versatile woody grass with over 1200 species, plays a critical role in the livelihoods of approximately 2.5 billion people globally, particularly in Asia, due to its diverse applications ranging from bioenergy production to construction and furniture manufacturing. Bamboo's significant potential in carbon farming and trading has garnered global attention. In the United States of America (U.S.A.), native bamboo species, collectively known as ''cane'', are represented by four species, including the historically abundant species giant river cane (Arundinaria gigantea). Historically forming extensive canebrakes in the southeastern U.S.A. and across 22 states, giant river cane is a resilient, perennial monocot capable of thriving across varied environments, from floodplains to mountain slopes. However, habitat loss due to agricultural expansion, urban development, overgrazing and fire suppression has reduced canebrake coverage to less than 2 % of its historical range. Giant river cane demonstrates exceptional environmental benefits, including sediment filtration, nutrient attenuation and habitat provision for diverse wildlife. Studies highlight its effectiveness in riparian buffers, significantly reducing sediment, nitrate and phosphorus levels in agricultural runoff, while its dense rhizome system aids in soil stabilization and water infiltration. Advanced propagation techniques, including rhizome planting and novel container-based methods, offer promising solutions for large-scale restoration of canebrakes, particularly in bottomland forest and riparian zones. Restoring giant river cane in degraded habitats not only supports biodiversity but also enhances ecosystem services, making it a critical component of riparian and agricultural land management. Giant cane’s contribution to ecological restoration is further supported by its impressive biomass production and carbon sequestration capabilities. In a 1720 m² plot, giant cane sequestered an estimated 5.8 metric tonnes of carbon, with a significant portion allocated to its below-ground system, emphasizing its role in soil stabilization and long-term carbon storage. Soil properties, such as calcium and phosphorus levels, also influence its growth dynamics, with soil calcium correlating with culm counts and cation exchange capacity affecting rhizome internodes. GIS-based site suitability analyses further enable targeted restoration efforts by identifying ideal conditions for giant cane growth. Future research should focus on optimizing propagation methods, evaluating its ecological impacts at watershed scales, and expanding its use in carbon trading frameworks to maximize its economic and environmental potential.